Determining the Effect of Group Flower Arranging Sessions on Caregiver Self-Efficacy and Stress Levels in an In-Patient Hospice. (December 2021) - Lavin, Joanne; Lavin, Claire; Bai, Xin; Mastropaolo, Stephanie; Feldman, Debbie
This study was designed to promote enhanced self-efficacy and decreased stress levels for family caregivers at a hospice care hospital, thus increasing their quality of life. This is achieved through group flower arranging sessions. The objectives are to (a) enhance self-efficacy scores for family caregivers of Calvary patients, (b) decrease stress levels for family caregivers of Calvary patients, and (c) disseminate results to other hospices. The results show that the flower arranging sessions resulted in significantly increased self-efficacy and decreased stress and associated problems for the caregiver participants. Implications and suggestions for future research are discussed.